Troy and Homer : towards a solution of an old mystery - Latacz, Joachim (OUP E-Books., 2004)
In this book Joachim Latacz, turns the spotlight of modern research on the much-debated question of whether the wealthy city of Troy described by Homer in the "Iliad" was a poetic fiction or a memory of historical reality. Earlier excavations at the hill of Hisarlik, in Turkey, on the Dardanelles, brought no answer, but in 1988 a new archaeological enterprise, under the direction of Manfred Korfmann, led to a radical shift in understanding. Latacz, one of Korfmann's closest collaborators, traces the course of these excavations, and the renewed investigation of the imperial Hittite archives they have inspired. As he demonstrates, it is now clear that the background against which the plot of the "Iliad" is acted out is the historical reality of the thirteenth century BC. The Troy story as a whole must have arisen in this period, and we can detect traces of it in Homer's great poem